Safety Performance Enhancement Scheme for Munition Storages by applying the Concept of Shallow Underground Configurations. Issue 3 (November 2021) - Han, Seungsu; Kwon, Jihye; Kim, Sungkon
Abstract: Practical demand for the expansion of military ammunition and explosives storage in both volume and number has been increased, but due to the regulations applying on safety distance that require those facilities to be isolated from a civilian presence there are constant complications that arise. Recent incidents include petitions to either alleviate said regulations or relocate several ammunition storage facilities neighboring civilian areas are further development. Two types of underground ammunition storage facilities wold be considered in practice; the first is the tunnel-type which is applicable to areas that have sufficient depth of the cover and the latter is the sub-surface type that retains a sufficient depth of soli layer which can especially be utilized in areas that do not meet clearance requirements nor have geographical limitations. For the sub-surface type storage, there are two construction schemes for construction to meet safety-distance requirements. The existing popular ECMs (Earth Covered Magazines) have shallow soil cover for just plantation camouflage that is not affect the pressure suppression effect due to the internal explosion. Therefore, the scheme of the increasing soil cover depth to some amount, if applicable, pressure and fragment suppression can be achieved. The open-cut method for new construction is easily applied for this purpose in the field. This study addresses the safety distance reduction effect by increasing the soil cover depth on the ECM type storage facility by applying theoretical and numerical analysis.